Mid-term contracting in Electricity Markets: What to consider in Market Design? - Karsten Neuhoff; Sebastian Schwenen (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Decarbonization goals of the European Commission foresee different future scenarios for the European power market of which all are exceeding 60% renewables in the power system.3 High shares of intermittent renewable sources require significant changes to the physical system and impact the profitability of conventional generation. While renewable remuneration mechanisms in many European power systems typically provide long-term revenue guarantees for 15-20 years, conventional generation assets combine mid-term contracts, covering between 1-4 years, and vertical integration to reduce revenue volatility and secure operation, re-investment, and closure choices. To this end the participants of the Future Power Market Platform reviewed the empirical situation with mid-term contracts, identified incentives to contract and discussed possible commercial and regulatory approaches to support MTC. The main conclusions are - For generation, mid-term contracts help to secure re-investment and inform closure choices – and thus contribute to generation adequacy - For load, mid-term contracts hedge energy (input) prices, improve revenue stability and inform (re-)investment decisions. It is however unclear whether load has capacity and incentives to sign sufficient MTC to meet needs from generation and from power systems perspective. - Commercial approaches to increase mid-term contracting volumes can comprise for example new contracts types like option contracts - Regulatory solutions to support MTC and coordinate investment in generation may amend existing regulation, such as with transmission contract design or retail market regulation - Obligations towards MTC can be seen as a capacity mechanism– but equally capacity mechanisms can undermine the ability of market participants to sign MTC and thus their own effectiveness.
Keywords: Q41; Q42; Q48; L94; L95; 330; electricity markets; Mid-term contracting; electricity markets; Mid-term contracting